Family planning in adolescence in the perception of nurses of the Family Health Strategy - Queiroz, Ingrid Nepomuceno Bezerra; Santos, Maria Cecília Freitas Cesarino dos; Machado, Maria de Fátima Antero de Sousa; Lopes, Maria do Socorro Vieira; Costa, Carmem Cemires Cavalcante (Rev Rene, 2010)
The aim of this study was to understand how the attendance of family planning to the adolescent happens on the point of view of nurses who work in the Family Healthcare Units (FHU) of the Regional Executive Secretariat VI in Fortaleza-CE. It is a descriptive study carried out with eight nurses of the FHU in March and April 2009. Semi-structured interviews were carried out and the data were organized through the discourse of the Collective Subject technique and analyzed with literary review. The results evidenced that the attendance to the adolescent occurs in these units, but not in a specific way. It is characterized by limited accessibility to contraceptive methods and fragility in the organization of the service, too much delay in client service besides lack of time or space to accomplish group activities.